PENGARUH KEBIJAKSANAAN EKONOMI DI BIDANG KEUANGAN DAN PERBANKAN TERHADAP PERMINTAAN UANG (Studi Kasus Indonesia Tahun 1978-1999) - Basuki, Agus Tri (Jurnal Ekonomi & Studi Pembangunan, 2001)
This research will focus on demand for money phenomena in Indonesia with Partial Adjustment Model (PAM). This model has two assumptions: first, inflation with adaptive expectation, assumption, and second, inflation with perfect anticipation assumption.For the first model, income coefficient can’t explain too much demand for money significantly. Probably, inflation explains to much about demand behavior or the existence of income variable (current and lagged) at the same time in this model.The second model has a better result, all coefficient have the signs like hypothesis theoretically and significant.